Chinese Herbal Medicine for Chemotherapy-Induced Leukopenia: A Systematic Review and Meta-Analysis of High-Quality Randomized Controlled Trials - Wang, Qing; Ye, Hui; Wang, Qiu-qin; Li, Wei-tong; Yu, Bei-bei; Bai, Ya-mei; Xu, Gui-hua (Frontiers in Pharmacology, 2021)
Aim: We conducted a systematic review of high-quality randomized controlled trials (RCTs) to assess the efficacy and safety of Chinese Herbal Medicine (CHM) for treatment of chemotherapy-induced leukopenia (CIL). Methods: Eight electronic databases were searched from the date of inception to November 4, 2020 for high-quality RCTs that met the requirements of at least four key domains of the Cochrane risk of bias (RoB) tool. Revman 5.3 was applied for the meta-analysis. Results: Fourteen RCTs involving 1053 patients were included. The pooled results showed that CHM + chemotherapy exerted greater beneficial effects on white blood cell (WBC), neutrophil (NEU), hemoglobin (Hb) and platelet (PLT) counts in addition to karnofsky performance scale (KPS) score, but showed no significant difference on granulocyte colony-stimulating factor (G-CSF) dosage compared with chemotherapy alone. Placebo (PBO) + chemotherapy and CHM + chemotherapy groups showed no significant differences in terms of reduction of the incidence of neutropenia. CHM + chemotherapy was superior to Western medicine (WM) + chemotherapy in improving WBC count, KPS score, infection amount, required G-CSF dose and incidence of leukopenia. In addition, no severe adverse events were observed in the fourteen RCTs. Conclusions: CHM in combination with chemotherapy could effectively improve the clinical symptoms of CIL when compared with chemotherapy alone or Western medicine + chemotherapy, except for comparing to PBO+ chemotherapy. While CHMs were generally safe for clinical use and exerted no severe side-effects in the fourteen RCTs, high-quality RCTs with larger sample sizes are essential to reduce study heterogeneity.